Effectiveness of hCMV, mEF1a and mAct promoters on driving of foreign gene expression in transgenic zebrafish - Alimuddin, .; Yoshizaki, G.; Carman, O.; Takeuchi, T. (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
Highly unsaturated fatty acids (HUFA), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have long been recognized for its beneficial effect for human health and development. The D6 fatty acid desaturase is generally considered to be the rate-limiting factor in HUFA biosynthesis. Here, as the first step of study, we conducted experiment to select an appropriate construct that allows higher expression levels of masu salmon (Oncorhynchus masou) D6-desaturase gene in zebrafish (Danio rerio) in order to increase its activity for synthesizing EPA/DHA. Salmon D6-desaturase cDNA (sD6) was separately ligated with human cytomegalovirus (hCMV), medaka elongation factor 1a (mEF1a) and medaka b-actin (mAct) promoters. The resulted construct was designated as hCMV-sD6, mEF1a-sD6 and mAct-sD6, respectively. Each of the constructs in circular DNA form was microinjected into 1-cell stage embryos at a concentration of 30mg/ml. Transgenic individuals were identified by polymerase chain reaction (PCR) and their expression levels were analyzed by reverse transcription PCR. The first (F1) and second (F2) generation was produced by crossing the transgenic founder F0 and F1, respectively, with wild-type fish. The results showed that the highest transient gene expression level was obtained from the mAct-D6 construct, followed respectively by EF1a-D6 and hCMV-D6 construct. The transmission rate of transgene into F1 generation was 4.2%-44.1%, and into F2 was followed the Mendellian segregation pattern. Expression of transgene in F2 generation was varied between strains regarding as the mosaics of F0 fish. Now, a transgenic system to study the modification of fatty acid biosynthesis pathways in fish was established. Further investigations are to produce fish containing higher levels of EPA and DHA. Keywords: desaturase, nutraceutical fatty acid, transgenic, zebrafish, masu salmon Abstrak Promoter merupakan regulator yang menentukan tempat, waktu dan tingkat ekspresi gen. Pada penelitian ini, kami melakukan seleksi kontruksi plasmid yang tepat yang menghasilkan tingkat ekspresi yang tinggi dari gen D6-desaturase-like ikan masu salmon (Oncorhynchus masou) yang ditransfer ke ikan zebra (Danio rerio) untuk meningkatkan kemampuannya dalam mensintesa EPA/DHA. cDNA D6-desaturase-like (OmD6FAD) dari ikan salmon masu diligasi secara terpisah dengan promoter dari cytomegalovirus manusia (hCMV), elongation factor 1a (mEF1a) dan b-actin (mbAct) dari ikan medaka, untuk membuat konstruksi plasmid yang berturut-turut disebut sebagai hCMV-OmD6FAD, mEF1a- OmD6FAD dan mbAct-OmD6FAD. Konstruksi tersebut dengan konsentrasi 30mg/ml disuntikkan ke embrio pada saat fase satu sel. Individu transgenik diidentifikasi menggunakan PCR dan tingkat ekspresi transgen dianalisa dengan RT-PCR. Hasil menunjukkan bahwa tingkat ekspresi sementara yang tertinggi dari gen asing adalah diperoleh dari konstruksi mbAct-OmD6FAD, diikuti selanjutnya oleh EF1a-OmD6FAD dan hCMV- OmD6FAD. Transgen telah ditransmisikan ke ikan generasi F2 dengan mengikuti pola segregasi Mendel. Tingkat ekspresi transgen yang tinggi pada jaringan ikan F2 yang diperiksa telah diperoleh. Dengan demikian, sebuah sistem transgenik untuk memodifikasi biosistesa asam lemak pada ikan telah dikembangkan. Kata kunci: promoter, desaturase asam lemak, transgenik, ikan zebra, ikan salmon masu